Effect of Biopsy Technique on the Survival Rate of Malignant Melanoma Patients - Yamashita, Yutaro; Hashimoto, Ichiro; Abe, Yoshiro; Seike, Takuya; Okawa, Katsumasa; Senzaki, Yuichi; Murao, Kazutoshi; Kubo, Yoshiaki; Nakanishi, Hideki (Archives of Plastic Surgery, 2014)
Background Cutaneous malignant melanoma has a poor prognosis. The detrimental effect of incisional biopsies on the outcome of malignant melanoma has been debated. The aim of this study was to determine the effect of the presence and type of biopsy on the prognosis of malignant melanoma.Methods The medical records of 109 malignant melanoma patients treated at Tokushima University Hospital from 1983 to 2007 were reviewed. After excluding 28 cases with stage 0 disease or incomplete data, 81 cases were analyzed in detail with respect to patient sex, age, tumor site, clinical stage at diagnosis, presence of ulceration or lymph node metastasis, and prognosis. The five-year survival and five-year disease-free survival rates of patients who underwent incisional or excisional biopsies were compared with those who did not undergo a biopsy.Results The male-to-female ratio was 1:1.19. The mean age was 61.3 years (range, 19-93 years). The most common site was a lower extremity, and the most common clinical stage was stage II. No significant differences in clinicopathological features, five-year survival rates, and five-year disease-free survival rates were observed among the three groups.Conclusions The presence and type of biopsy neither affected the metastatic rate nor the prognosis of malignant melanoma. The use of incisional biopsies is not encouraged because tumor thickness cannot be measured accurately. However, they may be helpful for confirming the diagnosis if an excisional biopsy cannot be performed.
Keywords: Melanoma; Prognosis; Survival rate